Needs of People Requiring Palliative Care in an Urban Area of Pondicherry, South India: An Exploratory Study - Praveena Daya A; Sonali Sarkar; Sitanshu Sekhar Kar (Medsci Publications, 2018)
Context: Diseases requiring palliative care are on rise and people suffering from these diseases experience pain, psychosocial dis- tress and other symptoms which decrease their quality of life. The study was conducted to assess the needs of people requiring pal- liative care in terms of medical, social, psychological, financial and spiritual aspects in two selected areas in Pondicherry. Materials and Methods: An exploratory descriptive study con- ducted among 3554 individuals in 1004 households in two selected areas under an Urban PHC in Pondicherry identified 22 people in need of palliative care and their needs were studied using Needs Assessment Tool: Progressive Disease (NAT: PD). Data was ana- lysed using IBM SPSS Software version 20. Levels of concern for various domains were rated subjectively as none, some, significant and expressed in proportions. Results: Major needs of the patients were in psychological domain followed by physical and financial domains. Common physical symptoms reported were sleep problems followed by fatigue or tiredness. Psychological problems reported were sustained lower- ing of mood followed by tearfulness. Financial problems reported were loss of income followed by costs of treatment and travel ex- penses. Conclusion: Early identifications of these needs help to alleviate the problems of patients and their dependents to a great extent.